Ceuta: muy bom sumydoiro de gente de uossa terra e darmas e de dinheiro - Antónia, Natália Maria (2015)
The maintenance and defence of the Moroccan city of Ceuta, since its conquest, in 1415, to the integration into the Spanish Crown in 1656, caused dilemmas for some monarchs and contributed for contradictory views. The letter of D. João III sent to the Council of Lisbon in 1534, can be construed as a testimony of the doubts and indecision of the Portuguese crown on the policy to be followed in North Africa. This article aims, through some numerical indicators of resources spent on the Moroccan city of Ceuta, to answer the following questions: Ceuta was really expensive for the Portuguese kingdom? To what extent, the enormous costs invested in the defence and supply were indissolubly linked to the causes of the conquest and the maintenance phases?